Modulation of Granulocyte Cells Development by VipAlbumin® Administration in BALB/C Mice with Diabetes Mellitus - Adi Pradana, Andi Rizki; Ibrahim, Mansur; Sasmito Djati, Muhammad; Rifa'i, Muhaimin (Journal of Tropical Life Science, 2015)
Diabetes mellitus is a metabolic disease that is caused either by the decrease of insulin secretion frompancreatic β cells or the insensitivity of target cells against insulin. High glucose levels (hyperglycemia condition)can trigger the formation of free radicals, the main cause of diabetes micro and macrovascular complications. Theformation of free radicals and AGE (advanced glycation end-products) is assumed to became the key factor in thedecline of granulocyte cell production as well as the disruption of these cells functional activity. The purpose ofthis research was to determine the role of VipAlbumin® in inhibiting the adverse effects of increased blood glucoselevels, which highly influence the production of granulocyte. This study was divided into in vitro and in vivostage. BALB/C mice were used as experimental animals at in vivo stage and induced to undergo diabetes through100 mg/kg BW streptozotocin (STZ) injection at the age of 5 days. VipAlbumin® administered orally for 14 days,which began when mice reached the age of 14 weeks. The administration of VipAlbumin® divided into 3 dosesi.e. 0,01664 mg/gr BW (1st dose), 0,416 mg/gr BW (2nd dose), and 10,4 mg/gr BW (3rd dose). The further step wasa flowcytometric analysis to see the development of granulocyte cells relative amount, which were isolated fromthe bone marrow. The result of this analysis shows that VipAlbumin® administration, particularly at the 2nd and3rd dose, were able to modulate granulocyte cells development in the bone marrow.